Influence of temperature upon effects of crotoxin and gamma-irradiated crotoxin at rat neuromuscular transmission - Gallacci, M.; Nascimento, N.; Rogero, JR; Vassilieff, V. S. (Elsevier B.V., 2000)
The influence of temperature upon the effects of crotoxin (CTX)? from Crotalus durissus terrificus venom, and gamma-irradiated (Co-60, 2000 Gy) crotoxin (iCTX) was studied in rat neuromuscular transmission 'in vitro'. Indirect twitches were evoked in the phrenic-diaphragm preparation by supramaximal strength pulses with a duration of 0.5 ms and frequency of 0.5 Hz. The phospholipase A(2) (PLA(2)) enzymatic activity of CTX and iCTX was assayed against phosphadityl choline in Triton X-100. At 27 degrees C, CTX (14 mu g/ml) did not affect the amplitude of indirectly evoked twitches. However, at 37 degrees C, CTX induced a time-dependent blockade of the neuromuscular transmission that started at 90 min and was completed within 240 min, iCTX (14 mu g/ml) was inneffective on the neuromuscular transmission either at 27 or 37 degrees C. The PLA(2) enzymatic activity of CTX at 37 degrees C was 84 and that at 27 degrees C was 27 mu mol fatty acid released/min/mg protein, and that of the iCTX at 37 degrees C was 39 mu mol fatty acid released/min/mg protein. Thus, it was concluded that the mechanism of detoxification of CTX by gamma radiation at the neuromuscular level relies on the loss of its PLA(2) enzymatic activity. 2000 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: Crotalus durissus terrificus; crotoxin; gamma radiation; neuromuscular transmission